NJI 2022
DOI: 10.48029/nji.2014.cv607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structured Teaching Programme on Knowledge of School Teachers regarding First Aid Management in Selected Schools of Bangalore

Abstract: Safe childhood is the foundation of a good future. Children face different kinds of accidents at school premises while playing. Prevention of these accidents and their management is essential. A study was therefore conducted among school teachers at Anekal Taluk, Bangalore to make them aware about different accidents of children at school premises and their first aid management. The sample consisted of 30 primary and higher primary school teachers selected by convenience sampling technique. The analysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to that it could be concludes that studied questionnaire of teacher's knowledge of first aids at primary schools improvements through applying the suggested educational program could be generalize on the studied population even though differences within socio-demographical characteristics variables, as well as differences with their experience variable for the study subject's group, and that are accounted in the study group. Such findings are supported by (9) who indicated that it is no significant relationship between teachers' knowledge after application of education program and their demographic characteristic at primary school in Bangalore city. Furthermore, our findings are consistent with the findings of a study conducted by (14) that found that first-aid knowledge among teachers was not statistically related to their personal characteristics.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…According to that it could be concludes that studied questionnaire of teacher's knowledge of first aids at primary schools improvements through applying the suggested educational program could be generalize on the studied population even though differences within socio-demographical characteristics variables, as well as differences with their experience variable for the study subject's group, and that are accounted in the study group. Such findings are supported by (9) who indicated that it is no significant relationship between teachers' knowledge after application of education program and their demographic characteristic at primary school in Bangalore city. Furthermore, our findings are consistent with the findings of a study conducted by (14) that found that first-aid knowledge among teachers was not statistically related to their personal characteristics.…”
Section: Discussionmentioning
confidence: 75%
“…So, the more certified teachers in first aid, the safer the community becomes and promotes a safer and healthier environment. Having staff and teachers who are well equipped with first aid skills contribute to reinforcing the safety of the schools (9) .…”
Section: Important Of the Studymentioning
confidence: 99%